Population dynamics of pink shrimp (Metapenaeus affinis) in Samboja Kuala Waters, Kutai Kartanegara Regency - Putri Handayani; Muhammad Syahrir Ramang; Abdunnur Abdunnur (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2024)
Samboja Kuala has a very wide sea and has abundant natural resources, pink shrimp (M. affinis) is one of caught in Samboja Kuala waters.  The pink shrimp catches operate at night, because the intensity of the jinga shrimp catch is high, the possibility of exploiting shrimp resources will be threatened.  This research was conducted in November-December 2022. Shrimp sampling was carried out using mini trawls operated in Samboja waters. The purpose of this study was to study the sex ratio, growth rate, death rate, pattern of new additions, and yield per recruitment.  The sex ratio of male and female pink shrimp was 1.00:1.40.  The growth rate coefficient (K) for male and female pink shrimp is 1.10/year and 0.53/year and the estimated asimtotik length of male and female pink shrimp (L∞) is 144.58, and 145.11.  The male and female pink shrimp obtained an exploitation result of E>0.5, which means that the catch of pink shrimp is classified as overfishing.  New additions to catches New additions to male pink shrimp occurred in May with a percentage of 34.69% and female pink shrimp in September 20.71%.  Y/R values ​​for male and female pink shrimp were 0.058/year and 0.23/year.